Should You Go Back to School? A Guide for Women - Lynn Max; Heidi Liss Radunovich (EDIS, 2008)
FCS-2287, a 4-page fact sheet by Lynn Max and Heidi Liss Radunovich, discusses issues surrounding returning to school in a question-and-answer format — advantages and disadvantages, how to pay for it, and factors contributing to success. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2008.